Young women's and men's climate adaptation practices and capacities in Kenya livestock production systems - Bullock, Renee; Miriti, Philip; DuttaGupta, Tanaya (Frontiers Media, 2023)
Climate change adaptation strategies specific to the livestock sector must be identified and tailored to diverse locations and livestock production systems to be effective. Social factors such as gender, wealth, age and education levels generate differentiated abilities and capacities to cope with climate shocks.In this study we draw upon 48 age and sex disaggregated focus group discussions with youth to understand young people’s engagement in the livestock sector and their livestock adaptation strategies. We first explore whether gender and locational differences exist in young women’s and men’s engagement in the livestock sector, specifically which livestock species young women and men rear. Next, we describe young women’s and men’s climate livestock adaptation strategies in mixed crop and livestock and agropastoral systems. Lastly, we share insights about specific relationships in different household arrangement that shape young women’s and men’s engagement in livestock during their transitions to adulthood. Youth rear certain species more than others, such as chickens and dairy cows. Livestock adaptation is generally low. Gendered practices during transitions to adulthood differ for young women and men and household relationships mediate young women’s and men’s livestock production engagement. intergenerational transfers are gendered, however, are changing in all locations. Women’s opportunities to inherit or acquire land, for instance, have expanded. Transitions into new households, however, often reinforce gendered access to resources and women’s labor. Recommendations on how to better develop inclusive and sustainable policies that provide support to youth in livestock and strengthen their adaptation capacities are provided.